2006
DOI: 10.1111/j.1525-1497.2006.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to veterans health administration care in a nationally representative sample of women veterans

Abstract: Findings highlight several domains in which VHA decisionmakers can intervene to enhance the care available to women veterans and point to a number of areas for further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 26 publications
(41 reference statements)
3
33
0
Order By: Relevance
“…For instance, women were far more likely to have received mental health and social services (most often on the same day) if they presented to the IC rather than UC clinic. This is important given women veterans' perceived barriers to care 40 , unique readjustment issues, and potentially greater mental health needs relative to male counterparts 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, women were far more likely to have received mental health and social services (most often on the same day) if they presented to the IC rather than UC clinic. This is important given women veterans' perceived barriers to care 40 , unique readjustment issues, and potentially greater mental health needs relative to male counterparts 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Former and current VHA users completed another measure that required them to rate the extent to which problems with a number of VHA characteristics interfered with their use of VHA care. 32 This measure addresses 3 domains, including problems with accessing women-specific/women sensitive care, problems with VHA doctors/staff, and problems with the ease of using VHA facilities. Items were rated using a 4-point response format, from "not at all" to "greatly."…”
Section: Methodsmentioning
confidence: 99%
“…In addition, these participants completed a measure that involved comparing their experiences and impressions of VHA care with those of other health care facilities on several dimensions, including the availability of services, doctors' skills and sensitivity, logistics of care, and facility characteristics. 32 Items were rated using a 5-point response format, from "much worse" to "much better." Mean scores were calculated for each of these 4 scales.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research examining PTSD among women Veterans has shown that women tend to report a higher incidence of military sexual trauma (MST) than men and higher symptoms of PTSD. 117 Additional barriers to engagement in treatment are also present for women Veterans and range from low income, a lack of womenspecific care, and the male-oriented nature of care at the VA. [117][118][119][120] For this reason, a women's Veterans program manager is identified and available at all sites who can help women Veterans receive needed service and advocate for the needs of women Veterans. In addition, gender-specific services are available for women Veterans, including Women's Stress Disorder Treatment Teams, specialized inpatient and residential programs for women, cohort treatment or separate wings for women, Women Veterans Comprehensive Health Centers, and Women Veterans Homelessness Programs.…”
Section: For Further Information)mentioning
confidence: 99%